MASALAH SOSIAL DAN KRITIK SOSIAL DALAM NASKAH DRAMA MONOLOG SARIMIN KARYA AGUS NOOR: SEBUAH TINJAUAN SOSIOLOGI SASTRA - Murti Wijayanti; Rusdian Noor Dermawan (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aims to describe the theme, plot, character and characterization, background, social problems, and social criticism in the Sarimin monologue drama script by Agus Noor. This study uses theory, approach, and methods of literary sociology analysis and a set of theories regarding themes, plot, character and characterization and setting. The social problem in the Sarimin monologue drama script by Agus Noor is the problem of poverty, which is to go to prison for being poor. The social criticism in the Sarimin monologue drama script by Agus Noor is social criticism among officials, namely social criticism on the governor and social criticism on selfish officials; social criticism on the law apparatus, which is that the police are often busy suddenly and about the police always belittling small people; and social criticism in the general public, namely the behavior of the Indonesian people who lack respect for their own culture and the Indonesian people easily forget.